Associations of indoor musty odors with depression and anxiety symptoms in Chinese older adults: a nationwide study - Xue Wang; Zhihua Yin; Qian Gao; Yunfeng Song; Hanchen Xu; Shuang Zang (BMC Public Health)
Abstract Background Indoor air pollution has been recognized as a risk factor for mental health, particularly depression and anxiety symptoms. Indoor musty odors are considered a component of indoor air pollution. However, evidence on the associations between indoor musty odors and mental health among older adults is limited. Methods The current study utilized data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). We employed self-reported data to ascertain indoor musty odors. Depression symptoms were evaluated utilizing the Center for Epidemiologic Studies Depression Scale-10 (CES-D-10), and anxiety symptoms were measured using the Generalized Anxiety Disorder Scale-7 (GAD-7). This study implemented logistic regression and linear regression to examine the associations of indoor musty odors with depression and anxiety symptoms. Results A total of 11,950 older adults (mean age = 83.11 ± 11.12 years) were included in this study. The study indicated that indoor musty odors were significantly associated with depression symptoms (adjusted odds ratio (OR) 1.83, 95% CI 1.58, 2.11) and anxiety symptoms (adjusted OR 2.12, 95% CI 1.78, 2.53). Conclusions These findings provide valuable insights of indoor musty odors into the potential health risks associated with older adults’ depression and anxiety symptoms.